(untitled) (Journal of the College of Basic Education, 2022)
The novel represents an essential source of poetic culture, which an ancient poet could not dispense with. It is a cultural construction on the one hand, and an important factor in the formation of poetics on the other hand, and its importance is evident in finding an artistic bond in the method or style between the poet-narrator and the one who narrates about him, as well as in creating a distinctive creative ability that may reach the poet-narrator to the level of virility. The novel in the houses of poetry, in which poets abound, acquires a clearer importance, as the sequence of poets in one house in a continuous format of the novel leaves its impact on their creativity. Kinship and womb that also bring them together